(Pro)renin receptor (ATP6AP2) depletion arrests As4.1 cells in the G0/G1 phase thereby increasing formation of primary cilia. Issue 7 (19th February 2017) - Wanka, Heike; Lutze, Philipp; Staar, Doreen; Peters, Barbara; Morch, Anica; Vogel, Lukas; Chilukoti, Ravi Kumar; Homuth, Georg; Sczodrok, Jaroslaw; Bäumgen, Inga; Peters, Jörg
Abstract: The (pro)renin receptor [(P)RR, ATP6AP2] is a multifunctional transmembrane protein that activates local renin–angiotensin systems, but also interacts with Wnt pathways and vacuolar H + ‐ATPase (V‐ATPase) during organogenesis. The aim of this study was to characterize the role of ATP6AP2 in the cell cycle in more detail. ATP6AP2 down‐regulation by siRNA in renal As4.1 cells resulted in a reduction in the rate of proliferation and a G0/G1 phase cell cycle arrest. We identified a number of novel target genes downstream of ATP6AP2 knock‐down that were related to the primary cilium ( Bbs‐1, Bbs‐3, Bbs‐7, Rabl5, Ttc26, Mks‐11, Mks‐5, Mks‐2, Tctn2, Nme7 ) and the cell cycle ( Pierce1, Clock, Ppif ). Accordingly, the number of cells expressing the primary cilium was markedly increased. We found no indication that these effects were dependent of V‐ATPase activity, as ATP6AP2 knock‐down did not affect lysosomal pH and bafilomycin A neither influenced the ciliary expression pattern nor the percentage of ciliated cells. Furthermore, ATP6AP2 appears to be essential for mitosis. ATP6AP2 translocated from the endoplasmatic reticulum to mitotic spindle poles (pro‐, meta‐ and anaphase) and the central spindle bundle (telophase) and ATP6AP2 knock‐down results in markedly deformed spindles. We conclude that ATP6AP2 is necessary for cell division, cell cycle progression and mitosis. ATP6AP2 also inhibits ciliogenesis, thus promoting proliferation and preventing differentiation.